Copper Nanoparticle in Cationized Palm Oil Fibres: Physic-Chemical Investigation - M. N. K., Chowdury; Beg, M. D. H.; Khan, Maksudur R.; M. F., Mina; A. F., Ismail (Springer, 2014)
At ambient atmospheric condition copper nanoparticles (CuNPs) were prepared in aqueous medium using copper chloride, sodium borohydride, ascorbic acid and polyvinyl alcohol (PVA) of two different molecular weights (M ws). The physical appearance of the prepared sol of CuNPs has been found to be stable for a couple of weeks when kept in ambient atmospheric condition, as confirmed by ultraviolet–visible absorption spectroscopy. Transmission electron microscopy exhibits spherical morphology of CuNPs with an average size of 3.5 ± 1.1 nm developed in the sol, where PVA of highM w renders smaller size (2.5 nm) than that of low M w. The synthesised CuNPs were embedded in palm oil fibres (POFs) via cationisation process. The cationisation of POF was ascertained by Fourier-transformed infrared and zero point charge determination. The inclusion of nanoparticles (NPs) onto the fibres’ surface has been consistently proven by Fourier transformed infrared spectroscopy, X-ray diffraction study, field emission scanning electron microscopy, energy dispersive X-ray study and thermogravimetric analysis. CuNP-coated POF showed the increment of tensile strength (∼34 %) and antifungal activity (24 %) with respect to control fibres. The observed findings suggest that NPs can be effectively used as reinforcing agents in natural fibres to improve their property and durability.